2014
DOI: 10.1017/s0317167100016188
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variability of Krabbe Disease Across the Lifespan

Abstract: Krabbe disease (galactocerebrosidase deficiency) is an inherited leukodystrophy that results in severe neurological defects due to altered myelination. Classically, disease onset is within the first year of life. Juvenile and adult-onset cases may have less classic presentations, making diagnosis difficult and often delayed. Here, we review the literature to demonstrate the hetereogeneity of presenting symptoms across all age groups. We also discuss diagnostic approach, emphasizing variation in biochemical, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…In addition, we did not measure brain atrophy, which is a known phenomenon in patients with Krabbe disease and those treated with transplantation. 6 The exclusion of brain atrophy from our data can possibly complicate our findings especially in regard to ventricular size as hydrocephalus ex vacuo is also seen in patients with brain atrophy. However, hydrocephalus ex vacuo is not associated with increased pressure; therefore, STV would not be expected in patients with hydrocephalus ex vacuo.…”
Section: Patients Without Stv Patients With Stvmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, we did not measure brain atrophy, which is a known phenomenon in patients with Krabbe disease and those treated with transplantation. 6 The exclusion of brain atrophy from our data can possibly complicate our findings especially in regard to ventricular size as hydrocephalus ex vacuo is also seen in patients with brain atrophy. However, hydrocephalus ex vacuo is not associated with increased pressure; therefore, STV would not be expected in patients with hydrocephalus ex vacuo.…”
Section: Patients Without Stv Patients With Stvmentioning
confidence: 81%
“…1,2 Although most patients present before the age of 12 months (early infantile onset), later-onset forms with more variable presentation, late infantile (12 months to three years), juvenile (three to eight years), and adult (eight years and older), have been well characterized. [3][4][5][6] Common presenting symptoms in early infantile Krabbe disease include regression of developmental milestones, irritability, developmental delays, feeding difficulties, and abnormal muscle tone. 3 The median survival rates in early infantile disease range from two to three years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two patients inherited this mutation from their father, who was heterozygous for the mutation. Interestingly, this mutation was reported in another patient with adult-onset, although no vision loss was reported [10,22] . The phenotype and genotype for the Krabbe disease shows considerable variation worldwide, which thereby rendering difficulty in accurate diagnosis [23] .…”
Section: Discussionmentioning
confidence: 99%
“…7,28 This genetic lesion was not noted in KD Japanese patients, instead, they show c.683_694del12insCTC or c.2002A > C (635_646del12insCTC and 1954A > C), representing approximately 30% of Japanese EIKD-associated alleles. 29 Recently, Liao et al 30 found that the symptoms of KD were heterogeneous across all ages of KD patients. EIKD was found to be the most prevalent form of KD among the Muslim Arabs and Druze communities, mostly due to the homozygous occurrence of two mutations: c.1582G > A (p.D528N) and c.1748 T > G (p.I583S), respectively.…”
Section: Introductionmentioning
confidence: 99%